2000
DOI: 10.1074/jbc.275.16.12223
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of N-Acetylcysteine and Nitric Oxide on Angiotensin II-induced Epidermal Growth Factor Receptor Phosphorylation and Intracellular Ca2+ Levels

Abstract: These studies describe inhibitory effects of N-acetylcysteine on several biochemical events associated with the activation of extracellular signal-regulated kinases (ERK) by angiotensin II in the cardiac fibroblast and compare these effects with those of the nitric oxide donor, S-nitroso-N-acetylpenicillamine, an agent we showed previously to inhibit angiotensin II-induced ERK activation and the concomitant phosphorylation of proline-rich tyrosine kinase 2 (Wang, D., Yu, X., and Brecher, P. (1999) J. Biol. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 27 publications
3
37
0
1
Order By: Relevance
“…Ang II has been shown to induce ERK 1/2 activation by both Ca 2ϩ /c-Src-dependent and -independent EGFR transactivation. 18,34,35 Our findings indicate that, in adult CFs, neither the EGFR nor c-Src is involved in signal transduction between the Ang II receptor and ERK 1/2, which distinguishes adult CFs from both neonatal CFs and VSMCs, which use EGFR transactivation.…”
Section: Discussionmentioning
confidence: 93%
“…Ang II has been shown to induce ERK 1/2 activation by both Ca 2ϩ /c-Src-dependent and -independent EGFR transactivation. 18,34,35 Our findings indicate that, in adult CFs, neither the EGFR nor c-Src is involved in signal transduction between the Ang II receptor and ERK 1/2, which distinguishes adult CFs from both neonatal CFs and VSMCs, which use EGFR transactivation.…”
Section: Discussionmentioning
confidence: 93%
“…29,30 Pu et al 29 demonstrated that ROS activated Src through selective phosphorylation at tyrosine 416 in NIH3T3 cells. Wang et al 31 showed that NAC inhibited Src phosphorylation at tyrosine 416 by Ang II in cardiac fibroblasts. Mukhin et al 32 mapped the major point of intersection to ROS to upstream of or at the level of Src in the Gi␤␥3 Src33 ERK pathway using 5-HT1A receptor-transfected CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this receptor was shown to mediate responses that are normally activated by tyrosine kinase-linked receptors as exemplified by those for EGF and PDGF. The transactivation of these two growth factor receptors by angiotensin II is mediated by ROS and inhibited by antioxidants such as N-acetylcysteine (212,246,458,607). Preliminary evidence suggests that angiotensin II-mediated transactivation of the EGF receptor involves the intermittant activation of the Src family kinase p60 c-src by hydrogen peroxide (591), which can directly activate p60 c-src in mouse fibroblasts (4; see sect.…”
Section: A Role Of Ros In Receptor-mediated Signaling Pathways: the mentioning
confidence: 99%